Formation of glassy phases and polymorphism in deep eutectic solvents - Alhadid, Ahmad; Mokrushina, Liudmila; Minceva, Mirjana (Journal of Molecular Liquids, 2020)
Deep eutectic solvents (DESs) are a class of eutectic mixtures that have very low melting temperature at the eutectic point, which limits crystallization or lead to formation of metastable polymorphs. This can produce a false estimate of the actual melting temperature of the mixture. The present work focuses on the formation of metastable phases in eutectic systems containing L-menthol. Differential scanning calorimetry (DSC) was applied to measure the solid–liquid equilibria (SLE) of the eutectic mixtures. Two sample-preparation methods were employed, namely annealing and in situ crystallization during the DSC run. We found that the eutectic temperature of the stable mixture is much higher than the observed glass-transition temperature of the mixture. Moreover, the eutectic temperature of a mixture with a stable polymorph is different from that of a metastable polymorph. The measured SLE data were correlated through non-ideality modeling using the non-random two-liquid (NRTL) equation. Our results show that SLE modeling is a useful tool for predicting the melting temperatures of stable mixtures without the need for time-consuming annealing methods. This work serves as a guide for reporting stable mixture properties when dealing with eutectic mixtures that form metastable phases.
CRIS-Team Scopus Importer:2020-07-10
Keywords: Deep eutectic solvents; Glass-transition temperature; Polymorphism; Solid–liquid equilibria